Programming Chrome apps - Rochkind, Marc J. (O'Reilly Media, Inc., 2014)
Put your web app design skills to work by learning how to create powerful and portable Chrome Apps. With this practical book, you'll learn how to build Google's unique apps to behave just like native apps so they can interact with hardware devices, access external files, and send notifications. Author Marc Rochkind takes you through a hands-on, objective tour of Chrome Apps, which run on any platform that supports the Chrome browser--including OS X, Windows, Linux, as well as Android and iOS. If you know how to work with HTML, CSS, JavaScript, and the DOM, you're ready to get started. Learn how to build, run, and debug Chrome Apps step-by-step Use Chrome Apps to access local files, sync files, and external files Take advantage of key-value-pair APIs, including sync storage and IndexedDB Use WebSockets, Google Cloud Messaging, and other networking methods Display graphics and images with Canvas, SVG, and the Media Galleries API Use alarms, context menus, location, the camera, Bluetooth, USB, and other APIs Publish apps to the Chrome Web Store with the Chrome Dev Editor.